2020
DOI: 10.3390/ani10112109
|View full text |Cite
|
Sign up to set email alerts
|

Urban Hedgehog Behavioural Responses to Temporary Habitat Disturbance versus Permanent Fragmentation

Abstract: Anthropogenic activities can result in both transient and permanent changes in the environment. We studied spatial and temporal behavioural responses of European hedgehogs (Erinaceus europaeus) to a transient (open-air music festival) and a permanent (highly fragmented area) disturbance in the city of Berlin, Germany. Activity, foraging and movement patterns were observed in two distinct areas in 2016 and 2017 using a “Before & After“ and “Control & Impact“ study design. Confronted with a music festiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…High human densities are associated with increasing habitat disturbance, which may impact hedgehog populations negatively. Acute human disturbance from park music festivals has been found to impact hedgehog movement and behaviours in Berlin (Rast et al 2019, Berger et al 2020), whilst hedgehogs in Bristol become more active after midnight, potentially to avoid exposure to pedestrian and vehicular traffic (Dowding et al 2010). Therefore, despite being found near to humans, these results suggest a threshold in hedgehog populations’ capacity to tolerate high levels of human activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High human densities are associated with increasing habitat disturbance, which may impact hedgehog populations negatively. Acute human disturbance from park music festivals has been found to impact hedgehog movement and behaviours in Berlin (Rast et al 2019, Berger et al 2020), whilst hedgehogs in Bristol become more active after midnight, potentially to avoid exposure to pedestrian and vehicular traffic (Dowding et al 2010). Therefore, despite being found near to humans, these results suggest a threshold in hedgehog populations’ capacity to tolerate high levels of human activity.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediate impervious cover may reflect the patchwork environment found in residential areas, with mixtures of housing and greenspace providing rich and varied habitat. Hedgehogs not only avoid impervious cover (Rondinini & Doncaster 2002, Dowding et al 2010, Braaker et al 2014) but also display behavioural capacity to tolerate habitat fragmentation and to traverse impervious surfaces within fragmented habitats (Berger et al 2020). It has been suggested that, excepting large roads, impervious cover does not pose a strong barrier for hedgehog movement (Rondinini & Doncaster 2002, Braaker et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to sex, season and environmental conditions, hedgehog movement behaviour also varies between urban landscapes (Dowding et al 2010a;Rasmussen et al 2019;Schaus Calderón 2021) potentially due to differences in building density (Schaus Calderón 2021), road type (Rondinini and Doncaster 2002) and disturbance levels (Berger et al 2020a). Irrespective of this, hedgehogs consistently favour back gardens (Baker and Harris 2007;Hof and Bright 2009;Dowding et al 2010a;Williams et al 2015Williams et al , 2018bRasmussen et al 2019;Gazzard and Baker 2020;Schaus Calderón 2021) and are thought to require access to around 13-14 back gardens per night (Rasmussen et al 2019;Schaus Calderón 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, a study in Berlin used GPS tracking and dataloggers and demonstrated a preference for movement in locations with lower light levels [ 35 ]. By attaching dataloggers to urban hedgehogs under different conditions, it was documented that the temporary disturbance of their habitat that was caused by a music festival had a more serious impact on hedgehog behaviour than a permanent disturbance caused by fragmentation [ 36 ]. Nevertheless, we stress the importance of further investigations on the effects of anthropogenic disturbances to the habitats before clear conclusions can be drawn.…”
mentioning
confidence: 99%